The Voices that Cannot Be Heard: A Phenomenological Study on the Lived Experiences of Deaf Teachers - Vicente, Marvin (JPAIR Multidisciplinary Research, 2020)
Employment is described as life-changing for Deaf people. To date, they have few and limited employment opportunities. This phenomenological study focuses on exploring deaf teachers’ lived experiences. It is crucial that we gain a better understanding of deaf teachers’ experience to generate a new area of focus on deaf people in the employment field. To gain insight into the nature of deaf teachers’ occupational experience, a focus group interview was conducted with 3 deaf teachers. Participants were gathered through chain referral sampling, also known as snowballing, where the researcher’s chosen participant recruits other participants who might participate in the study. The analysis of the data led to the emergence of six essential themes: (1) professional and personal attribution; (2) equality and inclusion in the workplace; (3) feeling of belongingness and relatedness; (4) support provider; (5) job satisfaction and motivation; and (6) difficulty and challenges. Findings of the study suggest that deaf teachers’ positive working environment and experience can be influenced by professional identity, personal attribution, accommodation, and inclusive practices, relatedness to significant others, support and network, job satisfaction and motivation, and ability to adapt to difficulties and challenges.